ANALISIS PENGARUH ECONOMIC VALUE ADDED (EVA) DAN RASIO KEUANGAN TERHADAP RETURN SAHAM SYARIAH - Sri Hariani, Lilik (Jurnal Ekonomi Modernisasi, 2010)
This research investigated the simultaneous impact and partial impact of financial ratios (ROA, ROE, EPS) and Economic Value-Added (EVA) on stock return. One of the four independent variables, that is EVA, are new concepts for measuring financial performance. Explanatory method was used in this research, and the sample was collected using purposive sampling method from Jakarta Islamic Index listed in Bursa Efek Indonesia (BEI, Indonesia Stock Exchange) for the period 2005 - 2007. Multiple linear regression was used for the analysis in this research.The result of the analysis shows that all independent variables, that is Return on Assets (ROA), Return on Equity (ROE), Earnings per Share (EPS) and EVA have both simultaneous and partial impact on the dependent variable, that is stock return. An interesting finding is that the regression coefficients are different among the variables. ROE and EPS were found to have positive and significant impact on dependent variable while EVA and ROA were found to have negative and significant impact on dependent variable. A positive value for ROE means that the ROE variable can be taken as a measure for a company’s effectivity in utilizing equity in the effort to gain profit. While EPS was found to have the most dominant impact on stock price. The higher the EPS, the greater management’s success in gaining profit for the shareholder or investors. ROA was found to have negative and significant. A finding of this research which is contrary to previous research is that economic value added (EVA) was found to have negative and significant impact on stock price. However this finding can be explained as follows: first, the average debt in the companies in the sample is greater than the value of their equity so that EVA will increase due to the reduction in WACC. The increase in EVA is accompanied by a reduction in stock return. Second, positive EVA is not accompanied by any increase of stock performance in the market; and third, stock prices in BEJ are affected more by non-fundamental factors. However, it should be noted that though a company may have negative EVA, but when the market believes that the company or the industrial sector of the company has a good future, then stock return will be high.